Transcriptomic analysis of FUCA1 knock-down in keratinocytes reveals new insights into the pathogenesis of fucosidosis skin lesions (2018)
Fucosidosis is a rare lysosomal storage disease which has been classified into two subtypes, depending on the severity of clinical signs and symptoms. Fucosidosis patients’ skin abnormalities include angiokeratoma corporis diffusum, widespread telangiectasia, thick skin, hyperhidrosis and hypohidrosis, acrocyanosis and distal transverse nail bands. It has been described that >50% of fucosidosis patients have angiokeratoma. At molecular level, fucosidosis is caused by lysosomal alpha-L-fucosidase (FUCA1) gene mutations. Obtaining samples for functional studies has been challenging due to the inherent difficulty in finding affected individuals. The effect of FUCA1 dysfunction on gene expression is unknown. The aim of this study was to analyse, in keratinocytes, the transcriptomic effect of FUCA1 knock-down for a better understanding of skin lesions’ pathogenesis affecting fucosidosis patients. FUCA1 knock-down (siRNA) was performed in human HaCaT immortalised keratinocytes. Affymetrix arrays and qPCR were used for analysing gene expression. Bioinformatics was used for functional clustering of modified genes. In total, 387 genes showed differential expression between FUCA1 silenced and non-silenced cells (222 up-regulated and 165 down-regulated). Up-regulated genes belonged to two major groups: keratinocyte differentiation/epidermal development (n = 17) and immune response (n = 61). Several transcription factors were up-regulated in FUCA1-siRNA transfected cells. This effect might partly have been produced by abnormal transcription factor expression, that is FOXN1. We thus propose that fucosidosis-related skin lesions (eg angiokeratoma) and those of other diseases (eg psoriasis) might be caused by dysfunctions in common aetiological overlapping molecular cascades. © 2018 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd